Magnetic Resonance Imaging of Hypertrophic Cardiomyopathy: Beyond Left Ventricular Wall Thickness. Issue 1 (February 2015) - Fattal, Julie; Henry, Marc-Antoine; Ou, Sopheap; Bradette, Simon; Papas, Konstantin; Marcotte, François; Garceau, Patrick; Pressacco, Josephine
During the past decade, cardiac magnetic resonance has gained increasing popularity in the diagnosis of hypertrophic cardiomyopathy because of its greater accuracy and better characterization of cardiac morphology compared with other imaging modalities. In this pictorial essay, a global clinical portrait of hypertrophic cardiomyopathy will be drawn. The various radiologic findings associated with each variant of hypertrophic cardiomyopathy, and the clinical edge offered by cardiac magnetic resonance will be discussed.